Impact of organic-inorganic color additive on the properties of ethylene-norbornene copolymer. (February 2020) - Marzec, Anna; Szadkowski, Bolesław; Kuśmierek, Małgorzata; Rogowski, Jacek; Maniukiewicz, Waldemar; Rybiński, Przemysław; Zaborski, Marian
Abstract: In this study, we developed a new organic-inorganic pigment (LP) by precipitation of dye molecules onto aluminum-magnesium hydroxide (LH). The morphology and physico-chemical properties of the pigment were characterized by X-ray diffraction analysis (XRD), secondary ion mass spectrometry (TOF-SIMS), 27-Al solid-state nuclear magnetic resonance (NMR) spectroscopy, scanning electron microscopy (SEM) and thermogravimetric analysis (TGA). The incorporation of the azo dye into the LH host caused an increase in the interlayer distances of the LP from 0.751 to 0.758 nm. The LP pigment also showed better thermal- and photo-stability than the pristine azo chromophore. The novel organic-inorganic additive was next applied as a filler at different concentrations (2 phr, 5 phr, 10 phr) to obtain colorful ethylene-norbornene (EN) films. The morphological, mechanical and flame-retardant properties of the composites were determined by XRD, SEM, dynamic-mechanical analysis (DMA) and cone calorimetry tests (CCT). The EN films containing the LH/Azo dye demonstrated improved mechanical, barrier and flame-retardant properties. Compared to the neat EN copolymer and EN/LH composite, the EN/LP sample was found to be the most resistant to UV aging, as confirmed by FTIR and mechanical analysis. Graphical abstract: Image 1 Highlights: Organic-inorganic pigment based on azo dye and inorganic host was obtained. Prepared pigment exhibited enhanced thermal stability and solvent resistance. EN/pigment composites showed improved flame retardancy and UV resistance.